2013
DOI: 10.1264/jsme2.me12074
|View full text |Cite
|
Sign up to set email alerts
|

Uranium (U)-Tolerant Bacterial Diversity from U Ore Deposit of Domiasiat in North-East India and Its Prospective Utilisation in Bioremediation

Abstract: Uranium (U)-tolerant aerobic chemo-heterotrophic bacteria were isolated from the sub-surface soils of U-rich deposits in Domiasiat, North East India. The bacterial community explored at molecular level by amplified ribosomal DNA restriction analysis (ARDRA) resulted in 51 distinct phylotypes. Bacterial community assemblages at the U mining site with the concentration of U ranging from 20 to 100 ppm, were found to be most diverse. Representative bacteria analysed by 16S rRNA gene sequencing were affiliated to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 41 publications
(53 reference statements)
3
43
0
Order By: Relevance
“…The significance of metal phosphorylation as a survival strategy for microorganisms is confirmed by our results of increased Ac/AlPA synthesis in more contaminated soils. Our results are in line with Kumar et al (2013) who showed that 76 % of the culturable bacteria isolated from U deposits possessed constitutive phosphatase activity, and Yung and Yiao (2014), who reported that AlPA is an enzyme which was neither induced nor inhibited by U contamination. Among the most common AlPA producers are members of Gammaproteobacteria, Actinobacteria, and Bacteroidetes (Kumar et al 2013), and all of these taxa along Acidobacteria were found in Bulgarian U polluted Buhovo and Sliven (Radeva et al 2013), and Senokos (unpublished data) mining sites with increasing share in the bacterial communities along the U and HM gradient of contamination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significance of metal phosphorylation as a survival strategy for microorganisms is confirmed by our results of increased Ac/AlPA synthesis in more contaminated soils. Our results are in line with Kumar et al (2013) who showed that 76 % of the culturable bacteria isolated from U deposits possessed constitutive phosphatase activity, and Yung and Yiao (2014), who reported that AlPA is an enzyme which was neither induced nor inhibited by U contamination. Among the most common AlPA producers are members of Gammaproteobacteria, Actinobacteria, and Bacteroidetes (Kumar et al 2013), and all of these taxa along Acidobacteria were found in Bulgarian U polluted Buhovo and Sliven (Radeva et al 2013), and Senokos (unpublished data) mining sites with increasing share in the bacterial communities along the U and HM gradient of contamination.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with Kumar et al (2013) who showed that 76 % of the culturable bacteria isolated from U deposits possessed constitutive phosphatase activity, and Yung and Yiao (2014), who reported that AlPA is an enzyme which was neither induced nor inhibited by U contamination. Among the most common AlPA producers are members of Gammaproteobacteria, Actinobacteria, and Bacteroidetes (Kumar et al 2013), and all of these taxa along Acidobacteria were found in Bulgarian U polluted Buhovo and Sliven (Radeva et al 2013), and Senokos (unpublished data) mining sites with increasing share in the bacterial communities along the U and HM gradient of contamination. Additionally, multi-metal (Cd, Co, Cr, Zn, and Ni (except DhA)) tolerance of AlPA and DhA is found than AcPA (Pb), determining the activities of AlPA and DhA as crucial for site cycling of OM and detoxification of metals, even in slightly acidic soils.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to indigenous microorganisms, the uranium tolerance of A. facilis was relatively moderate. Natural isolates from ore deposit in northeast India have displayed tolerances up to 4.0 mM [44].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of uranium that inhibited growth of various organisms like Deinococcus radiodurans, Escherichia coli, Pseudomonas putida, Caulobacter crescentus and Shewanella putrefaciens ranged from 500 μM to 3 mM (Hu et al 2005;Ruggiero et al 2005;Wade and DiChristina 2000). The minimum inhibitory concentration (MIC) for bacterial (aerobic, chemoheterotrophic) isolates from subsurface soils of uranium-rich deposits was found to be 4 mM (Kumar et al 2013a). The chemical toxicity studies for uranium have reported inhibition of growth of aquatic microflora including algae, cyanobacteria and other aquatic microorganisms at 4.2 μM in freshwater systems, whereas the bactericidal activity of this radionuclide is reported at a concentration of~420 μM (Driver 1994).…”
Section: Uranium Toxicity and Tolerancementioning
confidence: 99%
“…The gamma radiation dose was found to bẽ 11 μGy/h at a sampling site of uranium-rich deposit harbouring 5 mM of uranium (~1,200 ppm) (Acharya et al unpublished result). The strains isolated from such site showed high tolerance not only to uranium (4 mM) but also to various other heavy metals like copper, cadmium and lead (Kumar et al 2013a). …”
Section: Uranium Toxicity and Tolerancementioning
confidence: 99%